The Role of Procurement Biopsies in Kidney Acceptance Decision Making and Kidney Discard: Perceptions of Physicians, Nurse Coordinators, and OPO Staff and Directors. Issue 4 (10th March 2022) - Schantz, Karolina; Gordon, Elisa J.; Lee, Unsun; Rocha, Maria; Friedewald, John; Ladner, Daniela P.; Becker, Yolanda; Formica, Richard; Reese, Peter P.; Kaufman, Dixon; Barah, Masoud; Walker, Marissa; et al.
Abstract : Background: Procurement biopsies suffer from challenges with quality and reproducibility and are linked to kidney discard. Nonetheless, procurement biopsies are obtained for the majority of kidneys in the United States, and biopsy findings are commonly relied upon in kidney acceptance decisions. Methods: We conducted in-depth, semistructured interviews with 30 surgeons, nephrologists, nurse coordinators, and organ procurement organization (OPO) staff and directors to assess perceptions of factors contributing to kidney discard and strategies to reduce kidney discard, with a focus on the role of procurement biopsies. Thematic analysis was used to analyze qualitative data. Results: Three main themes emerged: (1) participants emphasized the importance of biopsy findings in making acceptance decisions but expressed concerns about a lack of standardization and quality control; (2) participants reported large variations in the level of importance placed on biopsy findings, the level of reliance on glomerulosclerosis in particular, and the cutoffs used; and (3) participants disagreed about how often procurement biopsies should be taken, with some supporting stricter limits on which kidneys are biopsied and others preferring a biopsy for most kidney offers. Conclusions: These findings support the development of standard practices for which kidneys require biopsy, how the biopsy material is prepared, and how the biopsy is interpreted. Variability in kidney acceptance practices across centers and the use of biopsy findings in guiding recipient selection also lend support to policies to allocate kidneys with suboptimal histological findings to the centers that are willing to use such kidneys and the patients who could most benefit from such offers.